The allometric relationships for estimating above-ground biomass and carbon stock in an abandoned traditional garden in East Kalimantan, Indonesia - Karyati Karyati; Kusno Yuli Widiati; Karmini Karmini; Rachmad Mulyadi (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Karyati, Widiati KY, Karmini, Mulyadi R. 2021. The allometric relationships for estimating aboveground biomass and carbon stock in an abandoned traditional garden in East Kalimantan, Indonesia. Biodiversitas 22: 751-762. The existence of traditional gardens after abandonment process has a role based on ecological and economic aspects. To estimate the biomass and carbon stock in the abandoned traditional gardens, specific allometric equations are required. The aim of this study was to develop allometric equations to estimate biomass of plant parts (leaf, branch, trunk, and aboveground biomass (AGB)) through tree dimensions variables (diameter at breast height (DBH), total tree height, and tree bole height). The relationships between stem biomass, AGB and tree dimensions were very strong indicated by the relatively high adjusted R2 value. The moderately strong relationships were shown between branch biomass and tree dimensions, meanwhile, the relationship between leaf biomass and tree dimensions was very weak. The specific allometric equations for estimating biomass and carbon stocks that are suitable for tree species and/or forest stands at a particular site are very useful for calculating the carbon stocks and sequestration. The appropriate biomass and carbon stock calculation are needed to determine policies related to global climate change.